Kecenderungan Perkembangan Teknologi Gasifikasi Biomassa: Studi Perbandingan di Beberapa Negara - Putera, Prakoso Bhairawa; Hermawati, Wati; Poerbosisworo, Ishelina Rosaira (Jurnal Sains dan Teknologi Indonesia, 2015)
Biomass gasification in one of the modern technology that was developed by thermochemical conversion. This technology has been developed in many countries. This paper gives an emphasis on developments and trends in the use of gasification technology in some countries (Finland, Denmark, Thailand, Sri Lanka, Cambodia), and learning for Indonesia as well. At least there are five things that could be the key to the success of implementation, namely the ongoing and continuous research and development, the involvement of all actors in research and development activities, the implementation focuses on a small scale first, the roadmap plans into the action with a strong financial support, and the human resources support at national and local levels.Gasifikasi biomassa merupakan salah satu teknologi modern yang dikembangkan melalui konversi termo kimia. Teknologi ini telah banyak dikembangkan di berbagai negara. Makalah ini memberikan penekanan pada perkembangan dan kecenderungan penggunaan teknologi gasifikasi di beberapa negara (Finlandia, Denmark, Thailand, Sri Langka, Kamboja), dan pembelajaran bagi Indonesia. Setidaknya ada lima hal yang dapat menjadi kunci keberhasilan implementasi, yaitu riset dan pengembangan berkelanjutan dan berkesinambungan, pelibatan semua aktor dalam aktivitas riset dan pengembangan, implementasi pada skala kecil dahulu, perencanaan peta jalan hingga aksi dengan dukungan pendanaan yang kuat, dan dukungan sumber daya manusia di tingkat nasional dan lokal.Keywords:Ã‚Â biomass gasification, technology trends,comparative study.